Is Small Always Beautiful? A Dialogue. (December 2016) - Pearson, Gordon; Parker, Martin
Abstract: For quite a few years the two authors have been engaging in dialogues about management issues. Using as a model Plato's dialogues between Socrates and his various students, we have tried to clarify the nature of a concept by asking questions and thinking carefully about the answers. We disagree about many things, but agree that we respect each other's opinions, and can clarify our own viewpoints by debating them respectfully with another. For this dialogue, we decided to focus on the question of the scale of business operations. One of us has a particular preference for small scale enterprise, and for the localisation of the economy, because he believes that the giganticism of corporations is behind many of the problems we face today. As you will see, the other protagonist disagrees, arguing instead that other issues than scale are at the root of why some businesses do bad things.